Prevalence of BRCA1/BRCA2 pathogenic variation in Chinese Han population. Issue 8 (28th May 2020) - Dong, Hui; Chandratre, Khyati; Qin, Yue; Zhang, Jing; Tian, Xiaoqing; Rong, Ce; Wang, Ning; Guo, Maoni; Zhao, Guoping; Wang, San Ming
Abstract : Background: Pathogenic variation in BRCA1 and BRCA2 ( BRCA ) is one of the most frequent genetic predispositions for hereditary breast cancer. The identification of the variant carriers plays an important role in prevention and treatment of cancer. Despite a population size of 1.4 billion and a quarter million annual new breast cancer cases, knowledge regarding the prevalence of BRCA variation in the Chinese population remains elusive. Methods: In this study, we used BRCA -targeted sequencing and bioinformatics approaches to screen for BRCA variants in 11 386 Chinese Han individuals, including 9331 females and 2055 males. Results: We identified 1209 BRCA variants, 34 of which were pathogenic, including 11 in BRCA1 and 23 in BRCA2 . These variants were distributed among 43 individuals (37 females and 6 males), with 13 carrying BRCA1 and 30 carrying BRCA2 variants. Based on these data, we determined a prevalence of 0.38%, or 1 carrier of a BRCA pathogenic variant out of every 265 Chinese Han individuals, and 5.1 million carriers among the Chinese Han population of 1.3 billion. Conclusion: Our study provides basic knowledge about the prevalence of BRCA pathogenic variation in the Chinese Han population. This information should be valuable for BRCA -related cancer prevention and treatment in the population.